BETWEEN IDEALS AND CHALLENGES OF ISLAMIC LAW IN THE DIGITAL AGE: - ismail ismail (State of Islamic Institute Langsa, 2021)
This article aims to explain the tendency to prepare digital prayer schedules and offer the ideal form in compiling digital prayer schedules in Indonesia. The results showed that digital prayer schedules in Indonesia today tend to be arranged in the form of one area with a geographical boundary of the district or city. Currently, there is no digital prayer schedule in one geographic area due to differences in choosing coordinate points as the base of calculation and not the same in using the value of iḥtiyāṭ. The ideal form in compiling a digital prayer schedule is to use the midpoint of the district or city in making the calculation headquarters, the value of the iḥtiyāṭ is adjusted to the area which is used, and astronomical data is taken at a time close to the time of prayer to be known.